Evaluation of a therapeutic combination to prevent ovarian hyperstimulation syndrome - Jaafar, Wissal; Fedhila, Abir; Kacem, Khadija; Chtourou, Sana; Chakroun, Nozha; Brahem, Marouen (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Ovarian hyperstimulation syndrome (OHSS) remains a significant iatrogenic complication in assisted reproductive technology. Various strategies have been proposed to minimize its occurrence, particularly in high-risk patients. To evaluate the effectiveness of a combined preventive protocol including GnRH antagonist protocol, GnRH agonist trigger, dopamine agonist (cabergoline), calcium infusion, and a freeze-all strategy in reducing the incidence of OHSS without compromising IVF outcomes. Methods: A comparative study was conducted on women undergoing IVF, divided into a study group receiving the combined protocol and a control group managed conventionally. Primary outcomes included stimulation parameters, incidence of OHSS, and biochemical pregnancy rates. Secondary outcomes assessed included the number of cumulus-oocyte complexes (COCs), mature oocytes (MII), and vitrified embryos. Results: The study group showed significantly lower gonadotropin doses, with improved ovarian response reflected by higher numbers of COCs, MII oocytes, and vitrified embryos (p<0.05). Despite these improved biological outcomes, β-hCG positivity rates did not differ significantly between the two groups (24% vs. 26.5%; p=0.239). No cases of moderate or severe OHSS were observed in the study group. Conclusions: The combined use of multiple evidence-based strategies appears effective in reducing the risk of OHSS while maintaining satisfactory IVF outcomes. This multifaceted approach may offer a safer stimulation pathway for high-risk patients without compromising pregnancy potential.